2021
DOI: 10.24843/jekt.2021.v14.i01.p04
|View full text |Cite
|
Sign up to set email alerts
|

Technical Efficiency of Independent Oil Palm Smallholder In Indonesia

Abstract: This study assesses technical efficiency and possible sources of inefficiency of independent smallholder oil palm production in Indonesia with stochastic frontier approach.  The result show all the input variables is  positively affect the oil palm production and exhibit decreasing returns to scale .  The farmers have mean technical efficiency (TE) values 0.6541, however about 53 % farmers have TE above 0.70. Factors such as age of farmer, education, extension services, member of farmer group,  land ownership … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 11 publications
3
2
0
Order By: Relevance
“…This is because the older farmers have more experience than younger farmers and they can improve the efficiency according to their experience. This finding is consistent with Hasnah et al, Fariani et al and Varina 9 , 17 , 21 . The planting system has a negative and significant value on technical inefficiency.…”
Section: Resultssupporting
confidence: 93%
See 3 more Smart Citations
“…This is because the older farmers have more experience than younger farmers and they can improve the efficiency according to their experience. This finding is consistent with Hasnah et al, Fariani et al and Varina 9 , 17 , 21 . The planting system has a negative and significant value on technical inefficiency.…”
Section: Resultssupporting
confidence: 93%
“…The more the farmers are educated, the more the technical efficiency. This is also in line with the finding of Alwarritzi and Varani et al, in which the higher the education level of palm oil farmers, the more responsive they tend to be in adopting and utilizing palm oil management technology 9 , 21 . Fariani et al and Varani et al also confirmed that the higher the level of farmer education reduces the level of technical inefficiency and the education increases the level of efficiency 9 , 21 .…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…In addition, they possess variations in financial management (Andrianto, Fauzi, & Falatehan, 2019) and low technical efficiency (Varina, Hartoyo, Kusnadi, & Rifin, 2021). Most independent smallholders do not record cash flows; only a few keep written records of the prices of fresh fruit bunches (FFB) or the quantity of fertilizers and pesticides (Sahara, Haryadi, & Kusumowardhani, 2017), have a low marginal propensity to save, and prefer to hold cash (Sahara et al, 2017).…”
Section: Introductionmentioning
confidence: 99%